The physiological and pathophysiological aspects of the maxillary sinus - Munjal, Manish; Gupta, Ritu; Sidhu, Joginder; Munjal, Shubham; Ahluwalia, Sahil; Bath, Mehak; Singh, Archit Pal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Among the paranasal sinuses the maxillary sinus with a bottle neck ventilatory and drainage pathway is the commonest sinus to be involved in inflammatory pathologies .With limited intervention at the osteo-meatal unit the disturbed intricate mucociliary physiology of the sinus tends to revert. The surgery being aptly captioned, the “functional endoscopic sinus surgery”. The unique physio-pathology of the maxillary sinus shall be elaborated.